Młodzież w rzeczywistości „globalnej zmiany” z perspektywy rówieśników - Kanclerz, Bożena (Kultura-Społeczeństwo-Edukacja, 2016)
The aim of this paper is to analyze students’ opinions about the contemporary generation of young people in the context of the transformation of the modern world, which are not without impact on the functioning of young people. Characteristics of global change society and the analysis of the syndrome society of late modernity has become the basis to approximate the results own research. The perception of youth from the perspective of their peers was one of the undertaken research problems in the study of life orientations of students. The article presents the opinions and views students about their peers, also in comparison with other results of research, which completes the picture of today’s youth, conscious processes and transformations of the modern world.